Short‐term administration of Polypodium leucotomos extract does not inhibit CYP3A4‐mediated metabolism of midazolam in healthy subjects: an open‐label, two‐period, fixed‐sequence study. (25th June 2022) - Shinya, Koichiro; Nishimura, Yuki; Ryu, Kakei; Sambe, Takehiko; Fujishiro, Masaya; Nakauchi, Akihiro; Kashiwabuchi, Yumika; Iwase, Mariko; Chokki, Hirokazu; Kurata, Norimitsu; Matsuyama, Takaaki; Kiuchi, Yuji
Abstract: The extract of Polypodium leucotomos is used as a dietary supplement for its ultraviolet radiation‐protective properties. Polypodium leucotomos extract reportedly inhibits CYP3A, which is important for drug metabolism in vitro in human microsomes and in vivo in rats. In this study, we explored the inhibitory effect of the P. leucotomos extract on CYP3A4‐mediated midazolam metabolism in humans. This open‐label, two‐period, fixed‐sequence study was performed on six healthy, Japanese, male volunteers. During period 1 (control), midazolam (1 mg) was orally administered. After a wash‐out period of at least 5 days, period 2 was initiated. Subjects ingested P. leucotomos extract (240 mg) once in the morning and once at noon on the day before midazolam administration, and once the next morning (thrice overall). Midazolam was administered as in period 1. Blood samples were regularly collected for 8 hours after drug administration, and serum midazolam concentration was determined by ultra‐fast liquid chromatography‐tandem mass spectrometry. The pharmacokinetic parameters of midazolam were calculated and compared between the two periods. The area under the concentration‐time curve was 19.18 ± 3.65 ng h/ml, maximum serum concentration was 7.81 ± 1.25 ng/ml, and half‐life was 2.32 ± 0.35 hours during period 2. These parameters did not differ from those recorded in period 1 (area under the concentration‐time curve: 18.74 ± 2.97 ng h/ml, maximum serum concentration: 8.78 ± 1.67 ng/ml, half‐life: 2.52 ± 0.52 h). Therefore, short‐term oral administration of P. leucotomos extract did not cause food‐drug interactions mediated by CYP3A4 inhibition in humans.